2017
DOI: 10.1002/ar.23724
|View full text |Cite
|
Sign up to set email alerts
|

HOXC13 and HSP27 Expression in Skin and the Periodic Growth of Secondary Fiber Follicles from Longdong Cashmere Goats Raised in Different Production Systems

Abstract: This experiment was conducted to identify periodic changes in secondary follicles (SFs) over one year of extensive (grazed) and intensive (housed and fed supplement) farming of Longdong cashmere goats. One-year old goats (n = 24, 12 extensively fed and 12 intensively fed) were studied. The diameter, depth, density, activity, and ultra-structural features of SFs were assessed using light microscopy and transmission electron microscopy. HOXC13 and HSP27 expression were studied using immunohistochemistry and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…This suggests hypoxia and low environmental temperature could delay entry of the SF into the anagen stage. These results support previous studies that suggested growth of SFs is influenced by the sunshine period and environmental temperature [21,26]. They also suggest that a warm environment and lower altitude may promote the growth of cashmere down fiber.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This suggests hypoxia and low environmental temperature could delay entry of the SF into the anagen stage. These results support previous studies that suggested growth of SFs is influenced by the sunshine period and environmental temperature [21,26]. They also suggest that a warm environment and lower altitude may promote the growth of cashmere down fiber.…”
Section: Discussionsupporting
confidence: 92%
“…HSP27 has previously been shown to be expressed in the epidermis [28][29][30] with levels of expression of this protein increasing with increased epidermal differentiation and trichilemmal keratinization [20]. A study of cashmere goats revealed that HSP27 protein expression may be influenced by the level of nutrition and, therefore, this protein may allow adaptation to adverse environment conditions [21]. In the present study, it was shown that HSP27 was present in all layers of the SFs, and the expression of HSP27 in Rikaze was higher than them in Huan County.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations